Mahmud az-Zamaxshariyning ma‘naviy-ma‘rifiy faoliyati - Raxmedova, M.A (SCIENCE and SOCIETY, 2023)
This article analyzes the life and work of az-Zamakhshari from the point of view of the pedagogical con- tent of the spiritual heritage, who in his youth constantly traveled from city to city, from country to country in order to ac-
Keywords: learning; scientific discussions; worldview; humility and manners; perseverance and patience; pleasure; science of interpretation; education; science; ignorant; spiritual and educational; cultural life; political subject; religious; political conflicts; public officials